2009
DOI: 10.1007/978-3-642-03816-7_32
|View full text |Cite
|
Sign up to set email alerts
|

Regular Expressions with Counting: Weak versus Strong Determinism

Abstract: We study deterministic regular expressions extended with the counting operator. There exist two notions of determinism, strong and weak determinism, which almost coincide for standard regular expressions. This, however, changes dramatically in the presence of counting. In particular, we show that weakly deterministic expressions with counting are exponentially more succinct and strictly more expressive than strongly deterministic ones, even though they still do not capture all regular languages. In addition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Regular expressions with numerical occurrence indicators have been investigated in the context of XML schema languages [15,14,22,23,29,28] since they are a part of the W3C XML Schema Language [21]. One of our PTIME upper bounds builds directly on Kilpeläinen and Tuhkonen's algorithm for membership testing of a regular expression with numerical occurrence indicators [28].…”
Section: Related Work and Further Literaturementioning
confidence: 99%
“…Regular expressions with numerical occurrence indicators have been investigated in the context of XML schema languages [15,14,22,23,29,28] since they are a part of the W3C XML Schema Language [21]. One of our PTIME upper bounds builds directly on Kilpeläinen and Tuhkonen's algorithm for membership testing of a regular expression with numerical occurrence indicators [28].…”
Section: Related Work and Further Literaturementioning
confidence: 99%
“…Regular expressions with numerical occurrence indicators have been investigated in the context of XML schema languages [Colazzo et al 2009b[Colazzo et al , 2009aGelade et al 2012Gelade et al , 2009Kilpeläinen andTuhkanen 2007, 2003] since they are a part of the W3C XML Schema Language [Gao et al 2009]. One of our polynomial time upper bounds builds directly on Kilpeläinen and Tuhkonen's algorithm for membership testing of a regular expression with numerical occurrence indicators [Kilpeläinen and Tuhkanen 2003].…”
Section: Related Work and Furthermentioning
confidence: 96%
“…Indeed, several people want to abandon the notion as its only reason for existence is to ensure compatibility with SGML parsers and, furthermore, because it is not a transparent one for the average user which is witnessed by several practical studies [8,16] that found a number of nondeterministic content models in actual DTDs. In practice, XSDs allow numerical occurrence constraints in their regular expressions, which complicates the definition of determinism even more [26,19]. In fact, Van der Vlist notes that Clarke and Murata already abandoned the notion in their Relax NG specification [54], the most serious competitor for XML Schema.…”
Section: Factormentioning
confidence: 96%